DARIA 1: Cosmic Fairy Tales - Rok Vilčnik, Rok (University of Maribor Press, 2023)
The English translation of Rok Vilčnik’s marvelously ethereal Cosmic Fairy Tales is the result of almost a decade of collaboration between the author, translation and English language students and their professor at the University of Maribor’s Department of Translation Studies, mature translators, English language professors, editors, and revisers. The book includes translations of 50 fairy tales by the acclaimed Slovenian writer, poet, and playwright Rok Vilčnik, aka rokgre, written between 1989 and 2020 and accompanied by the author’s original illustrations.